2006
DOI: 10.1021/bc050283q
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cell-Penetrating Peptides (CPPs) as Vehicles for Intracellular Delivery of Antisense Peptide Nucleic Acid (PNA)

Abstract: Cell-penetrating peptides (CPPs) are characterized by their ability to be internalized in mammalian cells. To investigate the relative potency of CPPs as carriers of medicinally relevant cargo, a positive read-out assay based on the ability of a peptide nucleic acid (PNA) oligomer to promote correct expression of a recombinant luciferase gene was employed. Seven different CPPs were included in the study: Transportan, oligo-arginine (R7-9), pTat, Penetratin, KFF, SynB3, and NLS. The CPP-PNA conjugates were synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 33 publications
6
124
1
3
Order By: Relevance
“…After 24 h of PNA treatment, we found that 1 Amol/L hTR13-R9 produced the maximum inhibition of telomerase activity, whereas treatment concentrations >1 Amol/L decreased cell viability (Supplementary Fig. S1A; data not shown), in general agreement with another study using cell-penetrating peptide-PNA conjugates (36). We further compared the inhibition of telomerase activity at <1 Amol/L of PNA hTR13-R9, LNA, and GRN163L in cells treated for 24, 48, and 72 h ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…After 24 h of PNA treatment, we found that 1 Amol/L hTR13-R9 produced the maximum inhibition of telomerase activity, whereas treatment concentrations >1 Amol/L decreased cell viability (Supplementary Fig. S1A; data not shown), in general agreement with another study using cell-penetrating peptide-PNA conjugates (36). We further compared the inhibition of telomerase activity at <1 Amol/L of PNA hTR13-R9, LNA, and GRN163L in cells treated for 24, 48, and 72 h ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…An increased number of arginine residues have previously been demonstrated to promote cellular uptake of CPPs (5,12), which most likely is a result of an improved hydrogen bonding between phospholipid headgroups in the cellular membrane and the CPP (7). However, earlier studies have also shown that an increased Arg content in a CPP negatively affects cell viability, possibly as a result of irreversible membrane perturbations mediated by the guanidinium groups (22,23). No decrease in viability was observed for PenArg in the concentrations employed in the present study (Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…It should be noted that the uptake studies described here track the accumulation and retention of the fl uorophore; thus, it is possible that this measurement might not refl ect accumulation of the oligonucleotide itself if the labels were to be cleaved. However, it has been our experience Kang et al, 2008) and that of several other laboratories (Turner et al, 2005;Bendifallah et al, 2006;El-Andaloussi et al, 2006) that fl uorophore labels placed at the 3′ position of stable oligonucleotides provide reasonably accurate tracking of oligonucleotides in cell culture experiments such as those described here.…”
Section: Endocytosis and Antisense Effects 105mentioning
confidence: 84%